Legal Perspectives on Underage Marriage in The Dayak Customary Society: Challenges and Human Rights Protection - Mulida Hayati; Rico Septian Noor (Universitas Islam Sultan Agung, 2026)
This study examines the conflict between state law and Dayak customary law regarding underage marriage practices. Using a legal pluralism framework and a socio-legal approach, this study analyses the customary rationality that legitimises these practices and their impact on human rights, particularly for women. The method used is empirical legal research, which fundamentally examines law in its social context. This choice is based on the research objective to understand how state law, particularly the Marriage Law, interacts and often conflicts with Dayak customary law that is alive and practised by the community. The results of this study show that customary marriage, driven by socio-economic factors and efforts to avoid communal sanctions, creates legal dualism that hinders children's access to fundamental rights to education and health. This study concludes that repressive law enforcement is ineffective and recommends an accommodative protection model.